Comparing the therapeutic efficacy of endoscopic minimally invasive surgery and traditional surgery for early-stage breast cancer: A meta-analysis - Ma Qiyi; Shi Tingting; Wang Huan; Xing Jie (Open Medicine)
Early-stage breast cancer requires effective surgical interventions. This meta-analysis compares the therapeutic efficacy of endoscopic minimally invasive surgery (EMIS) with traditional surgery, such as modified radical mastectomy.